Perancangan Sistem Monitoring Tetes dan Kapasitas Cairan Infus Kamar Pasien Menggunakan ESP8266 Berbasis Website dengan Framework Laravel - Mahesa Putra Baskoro Cahyo Ramadhan; Uyock Anggoro Saputro (STMIK Budi Darma, 2023)
Excessive nurse workload will result in errors in carrying out their duties, including during infusion. Late replacement of infusion fluids can be fatal for the patient, therefore a monitoring system is needed. The aims and objectives of this research are to realize the drip monitoring system program and patient room infusion capacity on the device using the Arduino IDE programming and website with the Laravel framework. This research used qualitative research with experimental methods on the NodeMCU ESP8266 Microcontroller, Photoelectric Speed Count Correlation Sensor (LM393), 168x64 OLED, Push Button and Load Cell sensors. Experimental research was also carried out on the design of tool system software or on the monitoring system. Researchers use the percentage error formula to find the error rate of the sensor. The results of error findings on the Correlation Photoelectric Speed Count sensor which were carried out 5 times obtained an error error of 0.56%, and on the Load Cell sensor an error error of 0.27% was obtained. In the results of testing the entire system that was built, the percentage results were 100%. From the test results, the Correlation Photoelectric Speed Count sensor and load cell work well on the programmed NodeMCU. This is proven in testing the tool for 1 hour with a set load cell weight factor that has been determined where the Correlation Photoelectric Speed Count sensor can read the drops of infusion fluids properly, namely the tpm value will decrease slowly according to the time the drops drop due to the air inside. bags of infusion fluids continue to decrease, as well as movement and blockages in the infusion set needles. In addition, the weight of the infusion bag will continue to decrease as the infusion of fluids to the patient progresses